Investigation on the effect of Friction Stir Processing Parameters on Micro-structure and Micro-hardness of Rice Husk Ash reinforced Al6061 Metal Matrix Composites - Fatchurrohman, Nanang; Farhana, N.; Marini, C. D. (IOP Publishing, 2017)
Friction stir processing (FSP) is an alternative way to produce the surface composites of aluminium alloy in order to modify the microstructure and improve the mechanical properties. In this experiment, Al6061 aluminium alloy has been chosen to be used as the matrix base plate for the FSP. Al606 has potential for the use in advanced application but it has low wear resistance. While, the reinforced used was rice husk ash (RHA) in order to produce surface composites which increased the micro hardness of the plate composites. The Al6061 was stirred individually and with 5 weight % of RHA at three different tool rotational speeds of 800 rpm, 1000 rpm and 1200 rpm. After running the FSP, the result in the distribution of particles and the micro hardness of the specimens were identified. The result showed that Al6061 plate with the existing 5 weight % of RHA reinforced at the highest of tool rotational speeds of 1200rpm has the best distribution of particles and the highest result in average of micro hardness with 80Hv.